Incidence and characteristics of venous thrombotic events in pediatric cancer patients: A 20-year experience in the Maritimes, Canada. (17th February 2017) - Asyyed, Zeina; MacDonald, Tamara; Digout, Carol; Kulkarni, Ketan
ABSTRACT: Objective : Venous thrombotic events (VTE) are a well-recognized complication in pediatric cancer patients. Population-based data on the incidence and characteristics of VTE in all pediatric cancer patients are limited. This information is crucial to identify patients at high risk and design targeted interventions accordingly. The present study was designed to determine the incidence and characteristics of VTE in the pediatric oncology population. Participants: We conducted a retrospective, population-based, cohort study of patients treated in the Maritimes, Canada between 1995 and 2015.Results : There were 1210 pediatric hematology/oncology patients from the Maritimes, Canada, treated at the IWK Health Centre between 1995 and 2015. Fifty-eight (4.8%) experienced at least 1 VTE and the majority of patients experienced it within 6 months of cancer diagnosis. The median age of patients who experienced VTE was 10.7 years (SD = 6.0). The most common presenting symptom of thrombosis was central venous line dysfunction, and the most common location for thrombosis was within the upper venous system. We observed that 65.6% of the patients with VTE required >1 central venous catheters (CVC). The presence of a VTE increased the odds of requiring >1 CVC to 3.6 (95% confidence interval: 1.76–7.3).Conclusion : Thus, in this large, population-based study, we present the incidence and characteristics of VTE in the pediatric oncology population and demonstrate the clinical impact of VTE in terms of loss of CVC. Larger, prospective studies are required to confirm these findings and to develop a risk model for managing and preventing VTE in this patient population.